OP0274 Recommendations for Screening and Detection of Connective-Tissue Disease Associated Pulmonary Arterial Hypertension. (23rd January 2014) - Khanna, D.; Gladue, H.; Fitzgerald, J.; Channick, R.; Chung, L.; Distler, O.; Furst, D.; Hachulla, E.; Humbert, M.; Langelben, D.; Mathai, S.; Saggar, R.; et al.
Abstract : Background: Pulmonary arterial hypertension (PAH) affects up to 15% of patients with connective tissue diseases (CTD) and is one of the leading causes of mortality in systemic sclerosis (SSc) and mixed connective tissue disease (MCTD). Previous recommendationswere developed as part of larger efforts in PAH and did not provide detailed recommendations in CTD-PAH. Objectives: To develop recommendations for screening and early detection of CTD-PAH using rigorous data-driven and consensus-building methodology. Methods: We performed a systematic review for the screening and diagnosis of PAH in CTD by searching available databases. Using the RAND/UCLA methodology, we developed case scenarios followed by 2 stages of voting—first one was voted anonymously by 10 international experts on 1 (inappropriate) -9 (appropriate) scale and 2 nd voting after face-to-face meeting. Results: The key recommendations include: All patients with SSc should be screened for PAH. MCTD or other CTD's with scleroderma features (referred hereon as scleroderma-spectrum disorders) should be screened similar to patients with SSc. Screening of asymptomatic patients is not recommended for MCTD or other CTD patients without features of scleroderma. RHC is mandatory for diagnosis of PAH. Acute vasodilator testing is not required as part of the evaluation of PAH in patients with SSc, SSc-spectrum disorders, or other CTDs. Initial screening evaluation in patients with SSc and scleroderma-spectrum disorders include pulmonary function test (PFT) including diffusion capacity carbon monoxide (DLCO), Transthoracic echocardiogram (TTE), NT- Pro BNP, and DETECT algorithm if DLCO% < 60% and >3 years disease duration. In SSc and SSc-spectrum disorders, TTE and PFT should be performed on an annual basis or TTE, PFT, and NT-Pro BNP if new signs or symptoms develop. Conclusions: We provide consensus-based and evidence-driven recommendations for screening and early detection of CTD-PAH. It is our hope that these recommendations will lead to early detection of CTD-PAH and ultimately improve patient outcomes. Disclosure of Interest: None Declared